Towards the Future of the Malay Community in Kelantan - Azli, Abdullah; Julaihi, Wahid; Kadhim, Fathel Khalil; Bouzid, Boudiaf (e-International Publishing House Ltd. United Kingdom, 2022)
The Malay settlement at Kota Bharu is on the brink of disappearance. This paper employs a mixed-method to indulge in the subject of the study. The finding illustrates that the Malay community withers with the cultural transformation due to development. This paper also reveals the life, essence, hopes, and aspirations of the Malays in the process of urbanisation. The process also presumably tests the survival of the Malays, who may be the subject of "museumification" in their own country in the future.